Legal Issues of Company Access Blocking Through Beneficial Ownership in Realizing Corporate Transparency in Indonesia - Widyarini Ardyanti; Rianda Dirkareshza (Jurnal Daulat Hukum, 2025)
This study examines the effectiveness of administrative sanctions in the form of blocking company access through the AHU Online system in increasing compliance with Beneficial Ownership (BO) reporting in order to realize corporate transparency in Indonesia, which is motivated by the still low compliance of companies in reporting BO data, which has only reached 50.27% of the total entities registered with the Directorate General of AHU. This study uses a normative juridical method with a statutory, conceptual, and case approach, as well as secondary data in the form of regulations and related legal literature. The results of the study indicate that the access blocking policy has provided a preventive effect on non-compliance with BO reporting, but its effectiveness is still hampered by weak data integration between agencies, technical system constraints, low awareness of business actors and even government officials. Therefore, it is necessary to strengthen digital verification, improve coordination between agencies, professionalism of public officials, and the establishment of a special authority for the AHU system to ensure data integrity and openness, so that public transparency and trust in the legal system and the business world can be increased.